Prospects of Implementation of the UN Convention against Torture in the Republic of Tajikistan - S. A. Rajabov (Московский журнал международного права, 2010)
The article considers the condition and prospects of implementation of the UN Convention against torture in the Republic of Tajikistan and necessity of ratification of the Optional Protocol to it. The article analyzes the norms of the criminal legislation of the Republic of Tajikistan responsible for implementation of such an act as torture and its conformity with international norms and obligations taken under the ratified UN Convention against torture. For effective counteraction with torture at the legislative level it is offered to add a new article to the Criminal Code of the Republic of Tajikistan. The structure of the crime and its elements such as the object, the objective side, the subject and the subjective side has been analyzed.